LATIM, PÚNICO E BERBERE NA ÁFRICA DO NORTE: IDENTIDADE E ALTERIDADE - Bustamante, Regina Maria da Cunha (PHOÎNIX, 2020)
This article proposes to the analysis ofhow, in the process of Roman domination of North Africa, latin became a t00l for lhe Roman power in lhe region.